A New Technique for Continent Urinary Diversion: Initial Experience and Description of the Technique - Del Biondo , Dario; Napodano , Giorgio; Di Giacomo, Ferdinando; Di Domenico , Dante Dino; Feleppa , Bruno; Yazici, Sertac; Zito, Aniello Rosario (Urology Journal, 2022)
PURPOSE: Orthotopic neobladder is a well-established surgical solution for continent urinary diversion after radical cystectomy. Nevertheless, it still represents a challenging surgery. Some critical issues of orthotopic bladder substitution include relevant complication rates, renal function impairment, urinary incontinence and patient quality of life. We present a new ileal neobladder technique, Vesuvian Orthotopic Neobladder (VON), performed for the first time at our institution in 2020. The main purpose of this new surgical procedure is to simplify and speed up the reservoir reconstruction through a ten standardized technical steps and obtain an appropriate bladder capacity at the same time. METHODS: Inclusion criteria were muscle-invasive bladder carcinoma or non muscle-invasive high risk bladder cancer patients fit for bladder substitution. The exclusion criteria were locally advanced cancer, presence of hydronephrosis, renal or hepatic impairment. A chest-abdominal CT scan and urinary cytology were performed before the procedure. Patients received neoadjuvant chemotherapy, as required. Overall, operative time, bladder reconfiguration time, hospitalization time, catheterization time were recorded. All complications associated with the procedure were classified according to the Clavien Dindo score. The bladder volume was evaluated by ultrasound three months after the surgery. RESULTS: A total of six male patients diagnosed with non-metastatic muscle-invasive or high-risk non-muscle invasive bladder cancer who underwent radical cystectomy followed by VON reconfiguration were included in the study. Mean age was 62.8 (±4.9) years; all selected patients enjoyed good health conditions (Charlson Comorbidity Index 4-6). One patient presented with high-risk non-muscle invasive bladder cancer. Four patients received neoadjuvant chemotherapy. Mean overall operative time was 273.3 (±18.6) minutes. Average time for neobladder reconstruction was 63.7 (±16.1) minutes. There were no intraoperative complications. A single case of urethral anastomosis leakage occurred and was treated conservatively. Bladder volume on ultrasound evaluation ranged between 250 and 290 ml. Day time and nocturnal continence were observed in four and three patients, respectively. CONCLUSION: The new VON technique is a good alternative to traditional orthotopic bladder procedures. VON reconstruction seems to offer the advantage of speeding up the procedure, reducing intestinal compromise with good storage capacity. The ten surgical steps can be considered a good starting point for further improvements in surgical technique. More robust data regarding the number of procedures and the duration of follow-up is required.